WC-CoCr coatings sprayed by high velocity oxygen-fuel (HVOF) flame on AA7050 aluminum alloy: electrochemical behavior in 3.5% NaCl solution - Magnani, Marina [UNESP]; Suegama, Patrícia Hatsue [UNESP]; Recco, Abel André Cândido; Guilemany, Josep Maria; Fugivara, Cecilio Sadao [UNESP]; Benedetti, Assis Vicente [UNESP] (ABM, ABC, ABPol, 2007)
In the present work, the electrochemical behavior of WC-CoCr coatings with 10 (W10), 15 (W15) and 20 (W20) torch passes sprayed by High Velocity Oxygen-Fuel (HVOF) flame on AA7050 aluminum alloy substrate, evaluated in 3.5% NaCl solution, were compared using open-circuit potential (E OC) measurements, electrochemical impedance spectroscopy (EIS) and polarization curves. The coating surfaces and their cross sections were characterized by X ray diffraction and the Rockwell-C hardness test, and also by optical (OM) and scanning electron microscopy (SEM) before and after the corrosion tests. The electrochemical data showed that sample W10 presented higher corrosion resistance than the others in chloride solutions. In some tests, aluminum salts on the coating surface were identified by EDS, indicating the corrosion of the substrate. and using aluminon, aluminum ions were detected and analyzing the surface via stereomicroscopy, hydrogen bubbles were observed, both showing that the electrolyte reached the substrate and galvanic corrosion possibly occurred. The physical characterization showed that sample W10 presented a lower number of cracks and pores, justifying its higher corrosion resistance.
Keywords: corrosion resistance; EIS; HVOF; WC-CoCr; aluminum alloy